INTERDISCIPLINARY, CURRICULUM AND TECNOLOGY: A STUDY ON THE PEDAGOGICAL PRACTICE IN THE ELEMENTARY AND MIDDLE SCHOOL - Mariana Aranha de Souza; Ivani Catarina Arantes Fazenda (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
In this study is discussed the relationship between curriculum, Interdisciplinarity, and Technology based upon an epistemological, methodological, and ontological perspective. Reasoned on the studies by Sacristán (2000), and Moreira and Silva (1990), this work reports the main theories to the curriculum and their applications on the everyday school. The interdisciplinary, supported by the work by Fazenda (2001,2014), points to the possible complementarity between knowledge and effectiveness of the partnership as essential to an intentional and contextualized practice. Valente (1993) and Silva (2002) stress out that the technology must be integrated into the curriculum and must contribute to the discussion that involves the everyday school.  Based upon a qualitative perspective, it is discussed two pedagogical practices carried out in computer labs in two classes of elementary and middle schools of a private school branch, one of the fifth and another of the eighth grades. The practices have shown: i) the importance of the partnership between teachers; ii) the need to work into thematics coming from critical perspective of the curriculum; and iii) the possibilities to use the technology offers pedagogical practices and development of the autonomy of students, which contribute to their formation and to the own formation of the teachers.